Glycosidation of betulinic acid using novozyme 435 - Abdu, Hamisu (2016)
In this study, 3-O-β-D-glucopyranoside-betulinic acid was successfully synthesized via the reaction between betulinic acid and glucose catalyzed by immobilized lipase from Candida antarctica (Novozyme 435) in t-butanol. The structure of the product obtained were elucidated using spectroscopic data. Effects of individual reaction parameters such as reaction time, reaction temperature, amount of enzyme and substrate molar ratio, were investigated and optimized. The optimum conditions for the reaction between betulinic acid and glucose were obtained at the reaction time of 48.50 h, temperature of 26oC, 175 mg of enzyme, and substrate molar ratio of 1:1.2; giving 85.83 % of yield. The Response Surface Methodology (RSM) based on five-level, three variables Central Composite Rotatable Design (CCRD) was employed using Design Expert software to evaluate the effect of synthesis parameters and its mutual interactions. It was observed that the maximum conversion yield of 3-O-β-D-glucopyranosidebetulinic acid 88.69% was obtained using 30.67 h, 54.30oC and 180 mg of enzyme using betulinic acid (0.05 mmol) and glucose (0.1 mmol) respectively. The experimental value obtained was 88.69%, closer to the results obtained using single parameter. Finally, the anticancer activity of the synthesized compound was evaluated against cultured mouse embryonic fibroblast normal cell line (3T3), human cervical carcinoma cancer (HeLa), human breast cancer (MCF-7), human T-promyelocytic leukaemia (HL-60), and cell lines. From the results, BA showed high activity against cultured human T-promyeloctic leukaemia (HL-60), human breast cancer (MCF-7), and human cervical carcinoma cancer (HeLa) cell lines with IC50 values of MCF-7 0.8 μg/ml, HL-60 4.4 μg/ml and HeLa 4.8 μg/ml, respectively. On the other hand, 3-O-β-D-glucopyranoside-betulinic acid also showed strong activity against cultured, HL-60, MCF-7and 3T3 with IC50 values of 8.4 μg/ml, 8.5 μg/ml and 2.75 μg/ml respectively. However, it was found to have moderate activity against HeLa cell line with IC50 value of 12.0 μg/ml. In conclusion, an enzymatic synthesis of 3-O-β-D-glucopyranoside-betulinic acid was successfully carried out by the reaction between betulinic acid and D-glucose in an organic solvent using Novozyme 435. The activity of 3-O-β-D-glucopyranosidebetulinic acid against cancer cell lines was found to be better than betulinic acid.